PENGARUH STRATEGI PEMBELAJARAN KONFLIK KOGNITIF TERHADAP PERUBAHAN KONSEPTUAL SISWA PADA MATERI LISTRIK DINAMIS DI SMA NEGERI 1 TANJUNG BATU - Meidahrianti .; Zulherman .; Taufiq . (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2014)
This study aimed to examine the effect of cognitive conflict learning strategies on students' conceptual change. This research was conducted in SMA Negeri 1 Tanjung Batu at even semester 2012-2013 academic year with the research subject is a class XA. The method used in this research is a pre - experimental methods with one group pre-test and post -test design. Data collection techniques used is a test. The tests used are also equipped with Certainty of Response Index (CRI) to look at students' conceptual change. Hypothesis test used is the t-test. The results of the analysis of the test data obtained tcount = 23.74 while the ttable = 2.03. Based on testing criteria, H0 is rejected, because of tcount > ttable, so it can be concluded that the learning using cognitive conflict strategy can affect students' conceptual change. N - gain or increase in students' understanding of concepts with high category is equal to 0.75 .